Online counterconditioning with COVID-19-relevant stimuli in lockdown: Impact on threat expectancy, fear, and persistent avoidance - Gemma Cuddihy (Journal of Behavior Therapy and Experimental Psychiatry, 2023)
Background and objectivesIn counterconditioning, a conditioned aversive stimulus (CS) is paired with an appetitive stimulus to reduce fear and avoidance. Findings are, however, mixed on the relative impact of counterconditioning versus standard extinction, where the CS is presented in the absence of the aversive event. This analogue treatment study investigated the impact of counterconditioning relative to standard extinction on threat expectancy, fear, and persistent avoidance with an online fear-conditioning task conducted with COVID-19-relevant appetitive stimuli during the pandemic.MethodsFollowing habituation, in which two CSs (male faces wearing face-coverings) were presented in the absence of the unconditioned stimulus (US; a loud female scream), participants (n = 123) underwent threat-conditioning where one stimulus (CS+) was followed by the US and another (CS-) was not. In avoidance learning, the US could be prevented by making a simple response in the presence of the CS+. Next, participants received either counterconditioning in which trial-unique positively rated images of scenes from before the COVID-19 pandemic and its associated restrictions (e.g., hugging others and holding hands) were presented with the CS + or no-counterconditioning (i.e., extinction). In the final test phase, avoidance was available, and all US deliveries were withheld.ResultsCounterconditioning led to diminished threat expectancy and reduced avoidance relative to no-counterconditioning. Fear ratings did not differ between groups.LimitationsNo physiological measures were obtained.ConclusionsImplemented online during the pandemic with COVID-19-relevant appetitive stimuli, counterconditioning was effective at reducing persistent avoidance and threat expectancy.